Binational Pearl Harbor? Tora! Tora! Tora! and the Fate of (Trans)national Memory - Marie Thorsten; Geoffrey M. White (Asia-Pacific Journal, 2010)
The fifty-year anniversary of the Treaty of Mutual Cooperation and Security between Japan and the United States, signed on January 19, 1960, was not exactly a cause for unrestrained celebration. In 2010, contentious disagreements over the relocation and expansion of the American military presence in Okinawa, lawsuits against the Toyota Motor Corporation, ongoing restrictions on the import of American beef, and disclosures of secret pacts that have allowed American nuclear-armed warships to enter Japan for decades, subdued commemorative tributes to the U.S.-Japan security agreement commonly known as "Ampo" in Japan.In this atmosphere it is nevertheless worth recalling another sort of U.S.-Japan pact marking the tenth anniversary of Ampo, the 1970 historical feature film, Tora! Tora! Tora! (dir. Richard Fleisher, Fukasaku Kinji and Masuda Toshio). Whereas the formal security treaty of 1960 officially prepared the two nations to resist future military attacks, Tora! Tora! Tora! unofficially scripted the two nations' interpretations of the key event that put them into a bitter war, the attack on Pearl Harbor in 1941. Although conceived by the American film studio Twentieth-Century Fox as a way to mark a new beginning for the two nations, certain popular opinions at the time, particularly in Japan, regarded Tora! Tora! Tora! as a cultural extension of the unequal security partnership.On the American side, Pearl Harbor has come to wield such iconic proprietorship that it may seem inconceivable that the authorship of such pivotal memory could ever be shared with the former enemy. Airing his vehement disapproval over whether to build a mosque near the site of the World Trade Center attacks, a controversy preoccupying Americans in 2010, political stalwart Newt Gingrich (former Republican Speaker of the House of Representatives), analogized, "We would never accept the Japanese putting up a site next to Pearl Harbor." In the realm of education, a series of teacher workshops that had brought American and Japanese educators together to discuss approaches to teaching about Pearl Harbor was recently brought to an abrupt end when an American participant complained to federal sponsors that the program amounted to "an agenda-based attack on the U.S. military, military history, and American veterans."4 The fact that this criticism, directed to the federal funding source (the National Endowment for the Humanities as well as the U.S. Congress) quickly found receptive audiences through political blogs and veterans groups' listservs suggests an insecure, zero-sum mentality in which listening to other controversies and points of view somehow erases dominant narratives, which must then be vigilantly protected.